Microbiota Transplant in the Treatment of Obesity and Diabetes: Current and Future Perspectives - Napolitano, Michael; Covasa, Mihai (Frontiers in Microbiology, 2020)
A wealth of evidence has revealed the critical role of the gut microbiota in health and disease. Many chronic diseases have been associated with gut microbiota imbalance in its composition, diversity and functional capacity. Several types of interventions have been shown to correct microbiota imbalance and restore the beneficial metabolic outcomes of a normal microbiota. Among them, fecal microbiota transplantation (FMT) is an emergent, promising technology employed to improve clinical outcomes of various pathological conditions through modifications in the gut microbiota composition. FMT has been used successfully as a treatment option in recurrent Clostridium difficile infection, a condition characterized by severe gut microbiota dysbiosis. However, the potential usage of FMT in other microbiota-associated conditions different from C. difficile such as metabolic syndrome or obesity that are also marked by gut dysbiosis is still under investigation. Furthermore, the contribution of the gut microbiota as a cause or consequence in metabolic disease is still largely debated. This review provides critical information on the methodological approaches of FMT and its technological innovation in clinical applications. This review sheds light on the current findings and gaps in our understanding of how FMT can be used as a future biotherapeutic to restore microbial homeostasis in amelioration of obesity and diabetes.